Factors determining successful education of children with autism spectrum disorder - Jokubaitienė, Toma; Ališauskas, Algirdas (Special Education, 2019)
In the paper, the favourable factors of the successful education of children with autism spectrum disorders have been analysed. The study confirms the uniqueness of the characteristics of children with autism spectrum disorders and their educational situations. Participants in the educational process - parents, teachers, speech therapists, psychologists, assistants, and classmates indicate both similar and different characteristics and needs of the same child. The uniqueness of the characteristics and individuality of the expression of peculiarities in children with autism spectrum disorders presupposes the importance of individualization of education. The study showed that educational success is determined by the favorable values and attitudes of the educators and friendly school community, as well as good knowledge of the child individuality, individualized education to address child’s needs and interests and to ensure his/her active participation. The collaboration of all educational participants, including the teacher, the child, the parents as well as the classmates has been found as one of successful educational factors.
Keywords: autism spectrum disorder; case study; successful education; participants of the education